The psychosocial impact on frontline nurses of caring for patients with COVID-19 during the first wave of the pandemic in New York City - Kovner, Christine (Nurs Outlook, 2021)
BACKGROUND: Infectious disease pandemics, such as COVID-19, have dramatically increased in the last several decades. PURPOSE: To investigate the personal and contextual factors associated with the psychological functioning of nurses responding to COVID in the New York City area. METHOD: Cross sectional data collected via a 95-item internet-based survey sent to an email list of the 7,219 nurses employed at four hospitals. FINDINGS: 2,495 nurses responded (RR 35%). The more that nurses cared for COVID patients as well as experienced home-work conflict and work-home conflict the higher the nurses' depression and anxiety. When asked what has helped the nurses to carry out their care of patients the most common responses were support from and to co-workers, training in proper PPE, and support from family/friends. DISCUSSION: Understanding the potential triggers and vulnerability factors can inform the development of institutional resources that would help minimize their impact, reducing the risk of psychological morbidity.